A seamlessly coupled GIS and distributed groundwater flow model. (August 2016) - Wang, Lei; Jackson, Christopher R.; Pachocka, Magdalena; Kingdon, Andrew
Abstract: There are three approaches for coupling groundwater models with GISs, i.e. loose, tight, and seamless . In seamless coupling a model code is written into, and run from within, a GIS. We implemented BGS GISGroundwater in a GIS in this way for the first time. It facilitates the construction and simulation of the model, and the visualisation of the results all within the GIS environment. The model consists of a 2D finite-difference groundwater flow model and a simple user-interface. It can represent heterogeneous aquifers, variably confined and unconfined conditions, and distributed groundwater recharge and abstraction. It offers benefits in terms of ease of use and in streamlining the model construction and application process. BGS GISGroundwater has been validated against analytical solutions to groundwater-head profiles for a range of aquifer configurations. This model lowers barriers to entry to groundwater flow modelling for a wider group of environmental scientists. Highlights: A seamless GIS-groundwater flow model is presented. It directly uses GIS data for groundwater flow modelling within the GIS environment. This easy-to-use and flexible model can be used by non-modellers. It is downloadable and can be used for any purpose free of charge. The model developed herein can be integrated into other raster GIS packages.